Determining inrush current limiting reactor for capacitor switching using PSCAD / Muhammad Hasanol Mustafa - Mustafa, Muhammad Hasanol (2009)
The switching of shunt capacitor banks at utility substations and on distribution feeders creates voltage and current transients in the power system which may be damaging to power system equipment. Transient over voltages due to the energizing of capacitor banks are the most common source of over voltages on many power systems. The high incidence of capacitor-switching induced over voltages is a result of a marked increase in the number of shunt capacitor banks used on transmission and distribution systems as well as the frequent switching thereof (in most instances at least one close open operation per day).The utility industry has undergone many changes over the years and one of the major power quality problems to utilities and their consumers is the transient voltages that are a result of capacitor bank switching. The energizing transient is important because it is one of the most frequent system switching operations. Distorted waveforms along with the harmonic pollution introduced to the system, may cause undesirable effects such as instability of converter control, increased system losses, an increase in motor losses, overheating in transformers, switchgear, capacitors and miss operation of protective relays, fuses, and metering devices. This paper explores the suitable calculated value for reactor in capacitor switching and the effect of inrush current in power distribution substation.